ANALISIS DAN REMEDIASI MISKONSEPSI SISWA MENGGUNAKANMULTIMEDIA INTERAKTIF BERBANTUAN TUTOR SEBAYA PADA TOPIK FOTOSINTESIS SEKOLAH MENENGAH ATAS - Rahmadyah Kusuma Putri; Fauziyah Harahap (Jurnal Pelita Pendidikan, 2016)
The objectives of this research are to analyze the students‟ misconceptions on topicphotosynthesis for each cognitive level and to know if the misconceptions remediation by usinginteractive multimedia and peer tutoringgive effect in decreasing students‟ misconceptionon topicphotosynthesis in SMA Swasta Nurul Iman Tanjung Morawa. Sample of this research are 56 studentsof science class XII. The types of this research are the descriptive research and pre-experimentalresearch with one group pretest-posttest design. The technique of data collecting was the two tiersmultiple choice closed reasoning diagnostic tests, consist of 45 questions which was used as pretestand posttest. The findingsshow that the students getting misconception on topic photosynthesis inhigh category of misconception by percentage 66%. The highest percentage of students‟misconception is at cognitive level 6, by percentage 76%. After treatment the results obtained thatmisconceptions remediation by using interactive multimedia and peer tutoring decrease students‟misconception as many as 47% which is from 66% to 19%. Hypothesis testing showed that tcount(3.969) > ttable (0.05)(55) (1.673), it means that H0 was rejected and Ha accepted. It can be concluded thatstudents‟ misconceptions remediation by using interactive multimedia and peer tutoring give effect indecreasing students‟ misconception on topic photosynthesis in science class XII SMA Swasta NurulIman Tanjung Morawa.Keywords: interactive multimedia, misconception, peer tutoring, photosynthesis